The experience of a nurse who survived a highly pathogenic novel arenavirus - Hayward, Andrea Rosemary (My University, 2015)
The purpose of the study was to explore and describe the experience of a nurse in a private sector hospital after contracting a highly pathogenic novel haemorrhagic fever from a patient and to explore the context of the environment in which she was cared for. Patients with complications from severe acute febrile diseases are admitted to intensive care units. During 2008, two patients with an unidentified disease were airlifted from Zambia and admitted to a private sector hospital in Johannesburg, South Africa. Four of five patients died in the outbreak before a diagnosis of Lujo virus was confirmed. Countries to the North and West of South Africa are known to be endemic areas of Viral Haemorrhagic Fevers (VHF). This puts South Africa at risk for imported VHF and future outbreaks. The sole survivor was able to share useful advice for future implementation from experiences during the period of her illness. Unique challenges of the management and environment of this outbreak may assist in future outbreaks. A bounded single case study design using mixed multiple qualitative approaches including phenomenology was used to underpin and guide the study of the participant’s experience. The participant’s reflection was subjected to in-depth analysis using Colaizzi’s framework. Triangulation using the reflection of the contents of the “Outbreak diary” – a journal kept by members of the managing team and clinical nursing records was undertaken. Emerging themes were grouped into four main themes: Initial contact with the source; Admission is inevitable; Moments of care and Always involved, which have been discussed in depth. The information gleaned from these themes can be applied to practice in future. The safety of patients and staff in an outbreak depends on attention to detail. History taking was identified as crucial for appropriate infection prevention methods to be put in place. Contact tracing and monitoring is key to containing an outbreak. The definition of contacts is based on the risk profile. Successful management requires coordination by a team of multi-skilled senior persons who have the authority to make decisions. As with all critically ill patients, the participant experienced many emotions. The lack of ability to control situations and care appeared to be important. Feelings of guilt still remain. A different meaning of kindness was exposed. Infection prevention and isolation is part of routine nursing practice and should be applied if there is an index of suspicion of a contagious disease. Care of patients with VHF is not routinely taught however maintaining basic principles may prevent spread and thus further cases. Support of and communication with all staff in the hospital is important for commitment. The setting in this study was a hospital in the private sector. The revelations of this case study can be used in future research to develop guidelines for use by the outbreak management team. They are intended to improve the management and emotional support of the health care workers as well as the victims and can be applied to outbreaks of any nature.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2015
Keywords: Orthomyxoviridae; Arenaviridae Infections